Formation of α‐SF5‐Enolate Enables Preparation of 3‐SF5‐Quinolin‐2‐ones, 3‐SF5‐Quinolines, and 3‐SF5‐Pyridin‐2‐ones: Evaluation of their Physicochemical Properties. (6th January 2016) - Joliton, Adrien; Plancher, Jean‐Marc; Carreira, Erick M.
Abstract: This study describes, for the first time, the generation of a SF5 ‐substituted ester enolate from benzyl SF5 ‐acetate under soft enolization conditions, which in turn participates in aldol addition reactions in high yield. The reaction was applied in the synthesis of 3‐SF5 ‐quinolin‐2‐ones, 3‐SF5 ‐quinolines, and 3‐SF5 ‐pyridin‐2‐ones, none of which have previously been reported. To provide guidelines for their use in drug discovery, the physicochemical properties of these building blocks were determined and compared with those of their CF3 ‐ and t ‐Bu‐analogues.